The Effect Predictor Elements Stimulus Response By Human Neural System Dimensions Sense, Feel, Think And Act On Customer Loyalty (Survey Of Fast-Food Restaurant Customers In Bandung) - Ramdan, Mohamad (2020)
Purpose: This research aims to know the influence of each dimension of Response of Human Neural System, namely Sense, Feel, Think, and Act on Customers Loyalty. Each dimension is analyzed into several manifest variables. The significance of the influence of Human's Neural System Response in general on Customers' Loyalty is also necessary to identify. Methodology: This study using SEM (Structural Equation Modeling) analysis, that used to resolve simultaneous multilevel models that cannot be resolved by the linear regression equation, and use the customer survey method to assess the indicators for each variable. Result: The result of the research shows several manifest variables that are influencing and not influencing the Customers' Loyalty. Dimensions of Human's Neural System Response that have influences on Customers' Loyalty, from the most significant to less significant, observed by the beta coefficient, is Sense, Think, Feel, and Act. The dominant predictor elements that entail in every regression model are room condition, exterior and interior design of the restaurant, and hospitality and politeness of the waiter, waitress, sales clerk, attendant, and other employees. It means that those variables have a dominant influence on customers' loyalty. Applications: This research can be used to support the development of management science studies in the field of marketing management, particularly those relating to the utilization of human nervous system responses and customer loyalty, as well as providing input to restaurant business decision makers in optimizing human nervous system responses in order to obtain and maintain customer loyalty. Originality: Research on customer loyalty shows that emotional factors (sense, feel, think, and act) are at the core of customer satisfaction and influence customer loyalty.